2018
DOI: 10.1002/ejhf.1153
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in heart failure without atrial fibrillation: gaps and dilemmas in current clinical practice

Abstract: Data from observational and post-hoc analyses suggest that heart failure (HF) itself may be associated with higher risk of thromboembolic events compared to populations without HF. Although oral anticoagulants (OACs) might be a therapeutic option in individual cases, anticoagulation therapy in HF patients in sinus rhythm is not generally recommended, as the implementation of OACs in clinical practice in this HF population is not supported by large randomized clinical trials to date. Indeed, the available data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Remote monitoring with intracardiac and wearable devices can detect atrial tachyarrhythmias and AF, both risk factors for stroke (23)…”
Section: Stroke: Rhythm and Risk Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote monitoring with intracardiac and wearable devices can detect atrial tachyarrhythmias and AF, both risk factors for stroke (23)…”
Section: Stroke: Rhythm and Risk Predictionmentioning
confidence: 99%
“…A subanalysis of the COMMANDER-HF trial also suggested that including venous thromboembolism in the thromboembolic endpoints could better identify the subset of patients with HF and SR who may benefit from antithrombotic therapy. 16 The CHA 2 DS 2 -VASc score (congestive HF, hypertension, age !75 years, diabetes mellitus, prior stroke or thromboembolism, vascular disease, age 65 to 75 years, and female sex)-used to stratify the risk of stroke in patients with AF 19,20 -can predict thromboembolic events (ischemic stroke, transient ischemic attack, and peripheral arterial embolism) similarly well in patients in SR, [21][22][23] as it reflects the abovementioned risk factors for thromboembolism in patients with HF and SR. Patients with AF and with two or more CHA 2 DS 2 -VASc risk factors have an almost threefold increased risk of stroke compared with those without any risk factors.…”
Section: Can Risk Stratification Identify Patients Who May Benefit Fr...mentioning
confidence: 99%
“…Meanwhile, the top three diseases for which warfarin was prescribed included CHF, CHF-AF, and AF. Warfarin administration to patients with CHF has proved to be able to reduce the risk of both systemic complications and venous thromboembolism (Siliste et al, 2018). The use of warfarin has also proved to be effective in preventing thromboembolism among patients with atrial fibrillation at I-A level of evidence (Katritsis et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This triad consists of blood stasis, endothelial disruption, and hypercoagulability. [4,5] In looking at HF patients who appear to be in sinus rhythm, they may carry a burden of subclinical atrial fibrillation contributing to thromboembolic events. [7] Thromboembolic risk stratification is important in HF with normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%